2016 IEEE 43rd Photovoltaic Specialists Conference (PVSC) 2016
DOI: 10.1109/pvsc.2016.7749860
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stability of highly conductive nominally undoped ZnO layers

Abstract: Abstract-Highly conductive nominally undoped ZnO (b-ZnO) films represent an attractive alternative for ZnO:Al windows employed in thin film solar cells. In order to assess their suitability for the PV industry, we examine here their stability in various environments. We show that the b-ZnO films can exhibit comparable stability to ZnO:Al films in both ambient and heated air. However, b-ZnO films degrade faster in accelerated open damp heat (DH) conditions, which can be related to their columnar microstructure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…2 in Ref. [22]. The broadening of the θ θ − 2 ZnO 002 diffraction peaks suggested that the thinner b-ZnO films possess a lower X-Ray coherence length, d XRD , as also depicted here in the legend of Fig.…”
Section: Dry Heat Ageingsupporting
confidence: 52%
See 1 more Smart Citation
“…2 in Ref. [22]. The broadening of the θ θ − 2 ZnO 002 diffraction peaks suggested that the thinner b-ZnO films possess a lower X-Ray coherence length, d XRD , as also depicted here in the legend of Fig.…”
Section: Dry Heat Ageingsupporting
confidence: 52%
“…It is to be underlined, that the optoelectrical properties of this b-ZnO stack are not significantly compromised by the overlayer presence [28], while its environmental stability is substantially improved. This is witnessed by the dry heat ageing experiments [22], and by the open DH analyses of unencapsulated solar cells equipped with the b-ZnO multilayers that are discussed in the next section. .…”
Section: Pathways Towards Stable B-zno Films: Multilayered B-znomentioning
confidence: 93%